Hubungan Antara Gaya Belajar dan Hasil Belajar Bahasa Inggris Kelas V SD Negeri 060967 Medan Belawan - Dody Feliks Pandimun Ambarita; Satri Sinaga; Permata Sari Br Siregar; Angeleva Sinaga; Patresia Situmorang; Riris Silalahi (Universitas Negeri Medan, 2025)
This research aims to determine the relationship between learning styles and English learning outcomes of fifth grade students of State Elementary School 060967 Medan Belawan. The method used in this study is a quantitative method. This type of research is correlational. The subjects of this study were fifth grade students at State Elementary School 060967 Medan Belawan, totaling 34 students with random sampling technique. Based on the results of the research that has been done, it can be concluded that the conditions for the hypothesis to be accepted based on the Product Moment correlation test are if thitung > ttabel, thitung = 0.486 and t table = 0.348, so H0 is rejected and Ha is accepted. Students with visual learning styles are 18 people (52.94%), auditory learning styles are 8 people (23.52%), kinesthetic learning styles are 5 people (14.70%), visual auditory learning styles are 1 person (2.94%), and visual kinesthetic learning styles are 1 person (2.94%). Thus, it can be said that the learning styles and English learning outcomes of class V of SD Negeri 060967 Medan Belawan have a relationship (correlation).